2016
DOI: 10.1093/humupd/dmw038
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte, embryo and blastocyst cryopreservation in ART: systematic review and meta-analysis comparing slow-freezing versus vitrification to produce evidence for the development of global guidance

Abstract: BACKGROUNDSuccessful cryopreservation of oocytes and embryos is essential not only to maximize the safety and efficacy of ovarian stimulation cycles in an IVF treatment, but also to enable fertility preservation. Two cryopreservation methods are routinely used: slow-freezing or vitrification. Slow-freezing allows for freezing to occur at a sufficiently slow rate to permit adequate cellular dehydration while minimizing intracellular ice formation. Vitrification allows the solidification of the cell(s) and of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
323
2
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(378 citation statements)
references
References 136 publications
(267 reference statements)
9
323
2
19
Order By: Relevance
“…A recent review showed a slightly favorable cryosurvival and clinical pregnancy rate for vitrification instead of slow-freezing as cryopreservation technique for embryos [37]. We solely use slow-freezing in our center, so this has no implication on our findings.…”
Section: Discussionmentioning
confidence: 92%
“…A recent review showed a slightly favorable cryosurvival and clinical pregnancy rate for vitrification instead of slow-freezing as cryopreservation technique for embryos [37]. We solely use slow-freezing in our center, so this has no implication on our findings.…”
Section: Discussionmentioning
confidence: 92%
“…Sin embargo, es variable el impacto que esta puede ejercer sobre la fertilidad(16)(17), probablemente muy en relación con la naturaleza del quiste, tipo de cirugía realizada y la experiencia del cirujano(18), además de la edad de la mujer y la edad que tenga en el momento de búsqueda de gestación. No obstante, el efecto que una nueva cirugía puede tener sobre la fertilidad y la alta eficacia de los programas de vitrificación ovocitaria en la actualidad (19) (20), lleva a contemplar la opción de la criopreservación de ovocitos ante cirugías ováricas repetidas.…”
Section: Discussionunclassified
“…Two cryopreservation methods are routinely used: slow-freezing or vitrification. In our work the method chosen was vitrification that has now become the method of choice for oocyte cryopreservation (4,5). The high request of heterologous fertilization (especially egg donation) and the improvements in cryopreservation techniques, stimulated centers of assisted reproduction in creating strategies for the collection, cryopreservation, transport abroad and use of gametes.…”
Section: Improvement Of Cryopreservation Techniquesmentioning
confidence: 99%